Temporal changes and risk factors for esophageal stenosis after salvage radiotherapy in superficial esophageal cancer following non-curative endoscopic submucosal dissection. (January 2022) - Nishibuchi, Ikuno; Murakami, Yuji; Kubo, Katsumaro; Imano, Nobuki; Takeuchi, Yuki; Urabe, Yuji; Oka, Shiro; Tanaka, Shinji; Nagata, Yasushi
Highlights: Esophageal stenosis improves after radiotherapy and ESD. The frequency of grade 3 esophageal stenosis was low, and grade 3 esophageal stenosis improved to grade 2 or less by EBD. No new ≥ grade 2 esophageal stenosis were observed 6 months after radiotherapy. Cervical esophageal cancer is a risk factor for severe esophageal stricture after combined ESD and RT. Abstract: Background and purpose: Radiotherapy (RT) has recently received increasing attention as an additional treatment for organ preservation after non-curative endoscopic submucosal dissection (ESD) in patients with superficial esophageal cancer. Esophageal stenosis is an adverse event related to RT after ESD that is not widely studied. The aim of this study was to investigate esophageal stenosis related to salvage RT in superficial esophageal cancer after non-curative ESD. Materials and methods: Fifty patients who received salvage RT after non-curative ESD at a single institution between 2011 and 2018 were included in this study. The Common Terminology Criteria for Adverse Events, version 5.0, was used to assess esophageal stenosis. Data were compared using Fisher's exact test. Statistical significance was set at P  < 0.05. Results: Median follow-up time was 48 months (range, 12–95 months). Grade 2 and 3 esophageal stenosis were observed in 17 (34%), and 3 patients (6%), respectively. The frequency of grade 2 or worse esophageal stenosis decreased over time (before RT, 6 months, 1 year, and 2 years after RT: 16 (32%), 13 (26%), 10 (20%), and 6 (12%) patients, respectively). Only one patient required endoscopic balloon dilation (EBD) 1 year after RT. All grade 3 esophageal stenosis improved grade 2 or less by EBD. In univariate analysis, only tumor location was a significant risk factor for grade 3 esophageal stenosis. Conclusions: Esophageal stenosis, after salvage RT in patients with esophageal cancer who received non-curative ESD, improved naturally or after EBD; only a few cases required long-term EBD.